Eczema: etiology, subtypes, therapeutic approaches and socioeconomic impact - Cuyler, Marizé; Twilley, Danielle; Lall, Namrita (Frontiers in Allergy, 2026)
Eczema is an inflammatory skin condition that affects individuals of all ages worldwide. Patients may develop various forms of eczema, including atopic dermatitis, contact dermatitis, which is often associated with an allergic response to various stimuli, dyshidrotic eczema which develops on the palms and soles, asteatotic dermatitis that predominantly occurs in elderly patients, nummular eczema characterized by its cylindrical shape lesions and seborrheic dermatitis often located on patient's scalps, back, face and chest. Extensive studies have been conducted on atopic dermatitis, however, limited information such as their etiology, effect on the immune system and potential treatments are available on the other types of eczema. The socioeconomic impacts of eczema include the cost of conventional treatments such as corticosteroids, immunosuppressive agents and phototherapy, expenses related to specialists’ consultation and the effect on work and school productivity. The impact of atopic dermatitis on patients’ quality of life, social functioning and individual healthcare expenses has been extensively studied in other countries but remains underreported in South Africa. Reports have estimated the annual direct and indirect costs in Australia, the United Kingdom and the United States, however reports are limited for South Africa. This study aimed to provide information on the different types of eczema's etiology, their respective socioeconomic impact in South Africa in correlation to the above mentioned inflated yearly cost, and conventional, targeted and alternative treatments commercially available. Several knowledge gaps were identified in this study, including the limited availability of information on asteatotic dermatitis, dyshidrotic dermatitis and nummular eczema, the effect most commercially available treatments have on other eczema subtypes and an in-depth review of the socioeconomic impact of eczema within the African continent.